2021
DOI: 10.4269/ajtmh.20-0306
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices regarding Leptospirosis among Visitors to a Recreational Forest in Malaysia

Abstract: Leptospirosis is a zoonotic disease and a worldwide public health problem that affects mainly high-risk groups. Characterizing knowledge, attitude, and practice (KAP) among high-risk groups is important to develop appropriate prevention programs. Here, we performed a cross-sectional study among 300 visitors of a recreational forest in Malaysia to examine leptospirosis KAP and demographics. These variables were integrated to create knowledge and practice scores for each respondent. All respondents had heard abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Other studies include obtaining data among visitors in the Lata Belantan recreational forest to assess their KAP levels. Most respondents demonstrated a high knowledge level (63%) and good practices (68%) in disease prevention, showing a direct correlation between high knowledge and preventive practices (Shafie et al, 2021). The study also found that by using informative signage in recreational areas can effectively communicate essential information about leptospirosis to visitors.…”
Section: Level Of Knowledge Awareness and Practices Towards Leptospir...mentioning
confidence: 76%
See 1 more Smart Citation
“…Other studies include obtaining data among visitors in the Lata Belantan recreational forest to assess their KAP levels. Most respondents demonstrated a high knowledge level (63%) and good practices (68%) in disease prevention, showing a direct correlation between high knowledge and preventive practices (Shafie et al, 2021). The study also found that by using informative signage in recreational areas can effectively communicate essential information about leptospirosis to visitors.…”
Section: Level Of Knowledge Awareness and Practices Towards Leptospir...mentioning
confidence: 76%
“…Besides reducing contact with the animal population, preventive interventions must focus on the current knowledge and awareness of the local population, particularly those at higher risk of infection (Shafie et al, 2021). While surveys may have been conducted in certain regions or countries to assess knowledge, attitude and practice (KAP) levels, there is limited comprehensive global survey specifically focused on leptospirosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of knowledge and attitude were insufficient to translate into good behavior practices. A study on visitors to a recreational forest in Terengganu state showed higher knowledge, positive attitudes, and good practices toward preventing leptospirosis [ 100 ]. However, most of them still had limited knowledge of the route of transmission and prevention measures.…”
Section: Level Of Leptospirosis Knowledgementioning
confidence: 99%
“…To date, no nationwide study in Malaysia has assessed the children's knowledge of diseases transmitted by pets and their pet-care practices. Most research targets adults and a single disease [5,13,1,40,42], excluding the study conducted by Rashid (2018). Nevertheless, Rashid (2018) targeted those aged 12 and older.…”
Section: Introductionmentioning
confidence: 99%